Correlation of body mass index, with cardiometabolic and cardiorespiratory fitness in health care professionals of Multan - Akhtar, Esha; Khan, Imran Ahmad; Perwasha, Perwasha; Ishaq, Shahid; Qurat-Ul-Ain; Arshad, Shumaila (Journal of the Pakistan Medical Association, 2024)
The current study was conducted at Ali-Ul-Murtaza Department of Rehabilitation Sciences, Muhammad Institute of Medical and Allied Sciences, Multan, Pakistan, from October to December 2022 to explore the correlation of body mass index with cardiometabolic and cardiorespiratory parameters in 393 male and female healthcare professionals, including physiotherapists, pharmacists and medical laboratory technicians, aged 22-40 years. The evaluation was on the basis of the Physical Activity Readiness Questionnaire, body mass index, lipid profile, body fat and correlation of blood pressure, temperature, oxygen saturation, respiration rate and heart rate with cardiorespiratory fitness assessed through shuttle-run test, step test and treadmill test. Data was analysed using SPSS 25. Of the 393 subjects, 140(35.62) were underweight, 140(35.62) were overweight and 113(28.75) were obese. Of the total, 153(38.93) were pleased with their general health, while 240(61.06) had a history of cardiovascular and metabolic conditions. ---Continue